Catholic Education in Progressive-Era San Francisco: Theory and Practice - Gribble, Richard (American catholic studies, 2009)
Approaching their work from different perspectives, Father Peter Yorke and Archbishop Edward Hanna led the drive to advance Catholic education in San Francisco between 1900 and 1935. While both men promoted the absolute need for Catholic schools, seeing them as an extension of the home and a bulwark for democracy, their different positions in the church provided varied manifestations of their support. For Yorke, a local pastor and well-known advocate for organized labor, education was the supreme work of the church. Indeed, schools were equally if not more important than churches. His generation of five educational textbooks crowned his work. Hanna, as leader of the archdiocese and Chairman of the Administrative Committee of the NCWC, saw education as vital to the transmission of the faith. On the national level he led the NCWC fight against the federalization of education. In California he championed efforts to give Catholic schools tax exempt status and fought against initiatives that jeopardized the freedom of church schools. Working independently, both men held Catholic education as second to none.